2019
DOI: 10.1186/s12891-019-2994-1
|View full text |Cite
|
Sign up to set email alerts
|

Is radiographic lumbar spondylolisthesis associated with occupational exposures? Findings from a nested case control study within the Wakayama spine study

Abstract: BackgroundTo explore the relationship between radiographic spondylolisthesis and occupational factors in a case-control study nested within the Wakayama Spine Study (WSS).MethodsThe WSS is a cross-sectional observational study amongst Japanese adults. All participants completed a lifetime occupational history and underwent X-rays of the lumbar spine (L1-S1) according to a pre-defined protocol. One trained surgeon graded the presence of a spondylolisthesis based upon ≥5% anterior or posterior slip at one or mor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
1
9
1
Order By: Relevance
“…This was also consistent with the observations of Ishimoto et al These authors showed that people under 75 years of age were less likely to develop spondylolisthesis if they climbed up stairs and slopes (≥1 h/day). Similarly, in the older group (≥75 years), walks of ≥3 km/day were a protective factor against a slip, in contrast to the observations of Denard et al [ 33 ]. It is worth noting that in the study by Denard et al, daily walking was a risk factor for a listhesis [ 9 ].…”
Section: Risk Factorscontrasting
confidence: 77%
See 2 more Smart Citations
“…This was also consistent with the observations of Ishimoto et al These authors showed that people under 75 years of age were less likely to develop spondylolisthesis if they climbed up stairs and slopes (≥1 h/day). Similarly, in the older group (≥75 years), walks of ≥3 km/day were a protective factor against a slip, in contrast to the observations of Denard et al [ 33 ]. It is worth noting that in the study by Denard et al, daily walking was a risk factor for a listhesis [ 9 ].…”
Section: Risk Factorscontrasting
confidence: 77%
“…In this case, patients who reported occupational driving for ≥4 h/day were more than two times more likely to develop spondylolisthesis. The situation was similar in the group of people aged ≥75 years who reported sedentary work for ≥2 h/day [ 33 ]. Additionally, some authors suggested a role of whole-body vibration, to which vehicle drivers were exposed as the main mechanism influencing the pathogenesis of a slip [ 71 , 72 , 73 ].…”
Section: Risk Factorsmentioning
confidence: 64%
See 1 more Smart Citation
“…This increased incidence is mainly attributed to the repetitive shear forces of hyperextension positions and the poor mechanics and alignment often used by young dancers to obtain their positions. Ishimoto et al [17] found, in a nested case-control study (722 vs. 605, mean age 70), that occupational driving and working in the agricultural/fishing industry were associated with radiographic spondylolisthesis (Odds ratio: 2.4 and 3.5, respectively). We indeed found a difference in the incidence rate between CU (1.8%) to AU (1%) and MU (0.8%), but those differences were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…However, agricultural and fishing industries had over 3-fold more spondylolisthesis cases than clerical and technical expertise. This association disappeared among those aged > 75 years [ 34 ]. We considered it inappropriate to limit fishers' lumbar burden to heavy lifting working time.…”
Section: Discussionmentioning
confidence: 99%